Association of Brain-Derived Neurotrophic Factor Gene Val66Met Polymorphism with Primary Dysmenorrhea - Lee, Lin-Chien (PLoS One, 2014)
Primary dysmenorrhea (PDM), the most prevalent menstrual cycle-related problem in women of reproductive age, is associated with negative moods. Whether the menstrual pain and negative moods have a genetic basis remains unknown. Brain-derived neurotrophic factor (BDNF) plays a key role in the production of central sensitization and contributes to chronic pain conditions. BDNF has also been implicated in stress-related mood disorders. We screened and genotyped the BDNF Val66Met polymorphism (rs6265) in 99 Taiwanese (Asian) PDMs (20–30 years old) and 101 age-matched healthy female controls. We found that there was a significantly higher frequency of the Met allele of the BDNF Val66Met polymorphism in the PDM group. Furthermore, BDNF Met/Met homozygosity had a significantly stronger association with PDM compared with Val carrier status. Subsequent behavioral/hormonal assessments of sub-groups (PDMs = 78, controls = 81; eligible for longitudinal multimodal neuroimaging battery studies) revealed that the BDNF Met/Met homozygous PDMs exhibited a higher menstrual pain score (sensory dimension) and a more anxious mood than the Val carrier PDMs during the menstrual phase. Although preliminary, our study suggests that the BDNF Val66Met polymorphism is associated with PDM in Taiwanese (Asian) people, and BDNF Met/Met homozygosity may be associated with an increased risk of PDM. Our data also suggest the BDNF Val66Met polymorphism as a possible regulator of menstrual pain and pain-related emotions in PDM. Absence of thermal hypersensitivity may connote an ethnic attribution. The presentation of our findings calls for further genetic and neuroscientific investigations of PDM.